Vikings. Season 6, Volume 2 [videorecording (Blu-Ray)] - Podz; Frazee, David (Filmmaker); Ludwig, Alexander, 1992-; Andersen, Alex Høgh, 1994-; Ilsø, Marco, 1994- (SDS, 2022)
Follows the adventures of the sons of legendary Viking, Ragnar Lothbrok, at the beginning of the Viking Age.